If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(s + -9) = -156 Reorder the terms: 10(-9 + s) = -156 (-9 * 10 + s * 10) = -156 (-90 + 10s) = -156 Solving -90 + 10s = -156 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '90' to each side of the equation. -90 + 90 + 10s = -156 + 90 Combine like terms: -90 + 90 = 0 0 + 10s = -156 + 90 10s = -156 + 90 Combine like terms: -156 + 90 = -66 10s = -66 Divide each side by '10'. s = -6.6 Simplifying s = -6.6
| 10d+3=7d+12 | | 4ln(3x+1)-x+3=0 | | 10+5h=2 | | 7(4s+5)=231 | | 5(2l+8)=60 | | (x/9)=(x/8) | | (u-6)*8=56 | | (q-9)*6=36 | | x-1+3x+3x+1=56 | | 63X^3/12X^2 | | x/9=x/8 | | -3x+4y= 64 | | 21y+2=8 | | -2(t-2)+6t=9-3 | | 10x^2+60x+250=0 | | 7x-(2-5x)=22 | | 4x-10=-1818 | | ((49-x)1.5)+x=65.72 | | 5/6=?/72 | | 5+4+5=450 | | 1=p-13 | | 9-4t=19 | | 2cos(2x)cos(x)=0 | | y-9x=54 | | 3x^2+4x+5=x^2+4x+23 | | 4x=7+2+5+14+7+7+4+3 | | (49-x)1.5=25.09 | | 2a(a+7)=2(a-3)2 | | 70-30y+10=0 | | 70+20y+10=0 | | 70-20y+10=0 | | |-2|=a |